Self-efficacy to use condoms, depression and sexual assertiveness in migrants - Ruiz Bugarin, Cynthia Lizbeth (2025)
Introduction: Research has identified certain key factors in human sexuality that can prevent health problems, such as HIV infection. Among these protective factors are self-efficacy to use condoms and sexual assertiveness. However, the existence of factors that promote risky sexual behaviors and that negatively impact emotional and mental well-being, in turn influencing general health, such as sexual depression, are also recognized. Objective: determine the relationship between self-efficacy to use condoms, sexual depression and sexual assertiveness in migrants. Material and methods: This is a correlational, cross-sectional study. The sample was made up of 249 people who migrate, who were selected from the population of migrants through non-probabilistic sampling, for convenience, in different social assistance centers for migrants. Three instruments were used to measure the variables. The Software Statistical Package for the Social Sciences version 20 was used to store and analyze the data. To know the characteristics of the participants, descriptive statistics and r-Spearman were used to determine the relationship between the variables. Results: 85.40% were men, mostly from Mexico (84.70%). A relationship was found between self-efficacy for condom use with sexual depression and sexual assertiveness, however no relationship was found between self-efficacy for condom use with the dimensions of sexual assertiveness. Discussion: The results obtained differ from some studies on sexual assertiveness due to various factors considering the study population. Conclusion: self-efficacy to use condom increases sexual assertiveness. Sexual depression decreases sexual assertiveness.